Whipworm-Associated Intestinal Microbiome Members Consistent Across Both Human and Mouse Hosts - Rosa, Bruce A.; Snowden, Caroline; Martin, John; Fischer, Kerstin; Kupritz, Jonah; Beshah, Ethiopia; Supali, Taniawati; Gankpala, Lincoln; Fischer, Peter U.; Urban, Joseph F.; Mitreva, Makedonka (Frontiers in Cellular and Infection Microbiology, 2021)
The human whipworm Trichuris trichiura infects 289 million people worldwide, resulting in substantial morbidity. Whipworm infections are difficult to treat due to low cure rates and high reinfection rates. Interactions between whipworm and its host’s intestinal microbiome present a potential novel target for infection control or prevention but are very complicated and are identified using inconsistent methodology and sample types across the literature, limiting their potential usefulness. Here, we used a combined 16S rRNA gene OTU analysis approach (QIIME2) for samples from humans and mice infected with whipworm (T. trichiura and T. muris, respectively) to identify for the first time, bacterial taxa that were consistently associated with whipworm infection spanning host species and infection status using four independent comparisons (baseline infected vs uninfected and before vs after deworming for both humans and mice). Using these four comparisons, we identified significant positive associations for seven taxa including Escherichia, which has been identified to induce whipworm egg hatching, and Bacteroides, which has previously been identified as a major component of the whipworm internal microbiome. We additionally identified significant negative associations for five taxa including four members of the order Clostridiales, two from the family Lachnospiraceae, including Blautia which was previously identified as positively associated with whipworm in independent human and mouse studies. Using this approach, bacterial taxa of interest for future association and mechanistic studies were identified, and several were validated by RT-qPCR. We demonstrate the applicability of a mouse animal model for comparison to human whipworm infections with respect to whipworm-induced intestinal microbiome disruption and subsequent restoration following deworming. Overall, the novel cross-species analysis approach utilized here provides a valuable research tool for studies of the interaction between whipworm infection and the host intestinal microbiome.